Wiedza o zasobach wewnętrznych a zachowania konkurencyjne małego przedsiębiorstwa transportowego - Nogalski, Bogdan; Szpitter, Agnieszka; Wójcik-Karpacz, Anna; Karpacz, Jarosław (Knowledge about the Internal Resources versus Competitive Behaviours of the Transport Small Business, 2008)
The purpose of this article is the identification of the range and the level of knowledge possessed by a small transportation enterprise about its own social sources assets which are essential to guarantee it a long-term development in the conditions of inconstancy and unpredictability of changes happening in its environment. In its empirical layer the case study of a small enterprise working Świętokrzyski region is presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 267-277